Entanglement due to Delayed Removal of a Buddy Wire. (29th December 2014) - Vorpahl, Marc; Seyfarth, Melchior; Tiroch, Klaus
Abstract : A buddy wire is often used to aid in the delivery of balloons and stents when negotiating tortuous or calcified vessels. We present a planned two-stent mini-crush intervention complicated by entanglement of the buddy wire with the second stent and subsequent distortion of the stent within the guiding catheter. Based on this case, we suggest removing the buddy wire immediately after successful positioning of the first stent, because entrapment with a second stent is possible and may lead to challenging situations in a simultaneous two-stent strategy.